The ex vivo antiplatelet activation potential of fruit phenolic metabolite hippuric acid. Issue 8 (5th August 2015) - Santhakumar, Abishek Bommannan; Stanley, Roger; Singh, Indu
<x xml:space="preserve">Abstract</x> Active metabolite of polyphenol intake, hippuric acid, reduces platelet activation-related conformational change and de-granulation ex vivo thereby alleviating thrombogenesis.